Transnasal endoscopic treatment of cerebrospinal fluid leak: 17 years’ experience - Presutti, L (Pacini Editore SpA, 2009)
Aim of this report is to describe the long-term results of endoscopic endonasal repair of cerebrospinal fluid leak using a septal mucoperichondrial graft. A case series of 52 patients operated for cerebrospinal fluid rhinorrhea between 1990 and 2006 is presented. All patients underwent surgical treatment for endoscopic endonasal closure of a cerebrospinal fluid leak using a septal mucoperichondrial graft. No lumbar drain and fluorescein tests were used. The intra-operative localization of the fistula was aided by Valsalva’s manoeuvre by the anaesthetist. The success rate, after the first attempt, was 88.5% (46/52 patients); for the remaining 11.5% (6/52 patients), a second attempt was necessary which proved successful in 5 cases, raising the overall success rate to 98.1% (51/52 patients). Relapse occurred in only one case (1.9%), after the second attempt. In conclusion, a free mucoperichondrial graft offered good results for cerebrospinal fluid leak repair. In the Authors’ experience, a high success rate can be achieved without the use of intrathecal fluorescein and lumbar drain.